2015
DOI: 10.1007/s12539-015-0266-9
|View full text |Cite
|
Sign up to set email alerts
|

Design of Potential RNAi (miRNA and siRNA) Molecules for Middle East Respiratory Syndrome Coronavirus (MERS-CoV) Gene Silencing by Computational Method

Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV) is a virus that manifests itself in viral infection with fever, cough, shortness of breath, renal failure and severe acute pneumonia, which often result in a fatal outcome. MERS-CoV has been shown to spread between people who are in close contact. Transmission from infected patients to healthcare personnel has also been observed and is irredeemable with present technology. Genetic studies on MERS-CoV have shown that ORF1ab encodes replicase polyprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
(42 reference statements)
0
29
0
Order By: Relevance
“…GO-based gene enrichment analysis demonstrated that many involved biological processes were closely related to the immune response ( Fig 3A ), including myeloid cell activation and neutrophil activation ( Fig 3C and 3E ). Interestingly, the miRNAs-related gene pathways were overexpressed as a response to SARS-CoV-2 infection, and they are known to play an important role against viral infection [ 19 ]. Activation of miRNAs as a defense mechanism during lung infection could be related to their important roles in physiological and pathological processes in the lung [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…GO-based gene enrichment analysis demonstrated that many involved biological processes were closely related to the immune response ( Fig 3A ), including myeloid cell activation and neutrophil activation ( Fig 3C and 3E ). Interestingly, the miRNAs-related gene pathways were overexpressed as a response to SARS-CoV-2 infection, and they are known to play an important role against viral infection [ 19 ]. Activation of miRNAs as a defense mechanism during lung infection could be related to their important roles in physiological and pathological processes in the lung [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of MERS-CoV the ORF1ab region encoding the replicase polyproteins plays a vital role in viral infection and therefore represents a suitable target for disease control. Four miRNA and five siRNA molecules were rationally designed by computational methods for silencing of nine different MERS-CoV strains for exploration of the treatment of MERS-CoV at the genomic level [124]. In attempts to optimize delivery of MERS-CoV siRNAs, transfection, electroporation and viral gene transfers have been applied.…”
Section: Gene Silencingmentioning
confidence: 99%
“…The design of siRNAs has also been based on analysis of nucleotide frequency at multiple locations in siRNAs [ 32 ] and the selection of effective siRNAs directed against conserved regions of HIV, hepatitis C (HCV), influenza virus and SARS-CoV [ 33 ]. The Viral siRNA Predictor was developed based on published data using features such as nucleotide frequency, thermodynamic factors and nucleotide location for prediction of siRNA targeting of pathogenic viruses [ 34 ]. However, the RNA structure might impose restrictions for RNA therapy based on properties of the HCV genome from primary sequence to tertiary structure [ 35 ].…”
Section: Rnai and Bioinformaticsmentioning
confidence: 99%